PENGARUH PARTISIPASI MASYARAKAT DAN TRANSPARANSI DALAM PENGELOLAAN DANA DESA TERHADAP PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DESA (APBDes) - Dhiu, Aurelia; Sayang, Sabulon; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2024)
The research objectives are as follows: 1. To determine the effect of community participation in managing village funds on the preparation of the APBDes in Bela Village. 2. To determine the effect of transparency in the management of village funds on the preparation of the APBDes in Bela Village. The type of research used in this research is quantitative research. In this study using multiple linear regression model test. The results of the study show the following data: 1. Community participation has an effect on the preparation of the Village Expenditure Budget (PBDes). The test results show that the coefficient value of the community participation variable (X1) is 0.393 with tcount > ttable (3.398 > 1.66235) 2. Transparency has an effect on the preparation of the expenditure income budget ja desa (APBDES). The test results showed the coefficient value of the transpiration variable (X2) was 0.524 with tcount > ttable (4.449 > 1.66235).